PELATIHAN USAHA MIKRO DAN KECIL (UMK) BIDANG KULINER DI KOTA BANDUNG - Sari, Puteri Andika; Chisti, Natalia; Marianti, Maria Merry; Fitriani, Katlea; Prasetya, Ivan (Divisi Pengabdian dan Pemberdayaan Masyarakat (DP2M) UNIKOM, 2024)
local economy. However, they face numerous challenges, especially following the COVID-19 pandemic. These challenges include increasing competition with the influx of new businesses, ineffective marketing strategies relying on traditional methods, and limited access to consistent raw materials. To address these issues, the Faculty of Economics at Parahyangan Catholic University, in collaboration with the First Baptist Church Bandung, organized a training and mentoring program for culinary MSEs. The program aimed to help MSEs adapt to market changes and enhance their competitiveness through various training sessions. Topics included product innovation to meet consumer trends, efficient supply chain management, digital marketing using social media and marketplaces, and workplace optimization to minimize waste. In addition to online training, participants received face-to-face coaching, providing personalized guidance to help them implement the knowledge gained. The results of the training showed significant improvements in participants' knowledge and skills, particularly in product diversification, digital technology adoption, and supply chain system enhancements. This program is expected to assist culinary MSEs in growing and competing sustainably in an increasingly competitive market.